Documenting Functional Use-Wear on Bone Tools: An RTI Approach. Issue 1 (22nd October 2021) - Desmond, Abigail; Cartwright, Ian; Allen, Richard
Bone tools have a long archaeological history, and have recently been shown to retain use-traces distinctive of different perishable crafting practices. When examined in a controlled way, these diagnostic use-traces can serve as proxies for the crafted forms the bone tools were used to produce (e.g., baskets, leather goods, etc.). However, a number of methodological stumbling-blocks have hindered the sharing of bone tool use-wear results in a consistent standardized format. We suggest the application of Reflectance Transformation Imaging (RTI), and provide details for how to construct an RTI system which resolves most problems related to reproducibility in use-trace analysis.